DEVELOPMENT OF AN INFORMATION SYSTEM FOR EVALUATING ACTIVITY EFFICIENCY BASED ON KPIs IN PRIVATE EDUCATIONAL INSTITUTIONS (International Bulletin of Applied Science and Technology, 2026)
This article examines the development of an information system based on KPI (Key Performance Indicators) to improve the assessment and management processes of performance in private educational institutions. The advantages of using modern information technologies in assessing the quality of the educational process in educational institutions, teacher performance, student results, and management efficiency are analyzed. The main elements of the KPI system, the architecture of the information system, functional modules and practical significance are also highlighted.